Penerapan Pendidikan Kesehatan Fisik dan Mental Dengan Pendekatan Saintifik Booklet Yoga Fital Kuat (Ayo Jaga Kesehatan Fisik dan Mental dengan Berperilaku Sehat) Dalam Upaya Meningkatkan Kesehatan Masyarakat - Indra Ruswadi; N. Yulianingsih; Nafisah Itsna Hasni; Masliha Masliha (FKIP, Universitas Palangka Raya, 2023)
Measures to prevent disease, personal hygiene, choosing food, sanitation, and so on. Should be done with a healthy behavior. In order for the public to understand healthy behavior, it is carried out by applying the Strong Fital Yoga Booklet Scientific Media (Let's Take Care of Physical and Mental Health by Behaving Healthy). The purpose of the Community Service activities is so that PKK cadres in Eretan Kulon Village, Kandanghaur District, Indramayu Regency understand: 1) How to maintain Physical and Mental Health by Behaving Healthy, 2) How to use the Strong Fital Yoga Booklet (Let's Take Care of Physical and Mental Health by Behaving Healthy ), 3) How to educate the public about the importance of maintaining physical and mental health. The method used in PKM activities is carried out through training on the importance of maintaining physical and mental health by healthy behavior as well as explaining how to use the Booklet entitled Strong Fital Yoga with the mentoring model. Results: Availability of supporting media for PKM in the form of a Strong Fital Yoga Booklet, Implementation of training and outreach especially related to the use of a Strong Fital Yoga Booklet. There are HKI documents and reporting. Conclusion: PKM activities run smoothly and there is positive support from partners, Partnerships run well and smoothly and partners are happy to accept the booklet innovation product entitled Yoga Fital Strong. Recommendation: Partners should provide health education to the community both at the Posyandu and outside the Posyandu, paying attention not only to the physical aspect but also to the mental problems, this is because being healthy is not only seen from the physical aspect but also the mental and other aspects.